2015
DOI: 10.1016/j.bbamcr.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 is necessary for the adipogenic differentiation of human mesenchymal stem cells

Abstract: CK2 is a serine/threonine protein kinase, which is so important for many aspects of cellular regulation that life without CK2 is impossible. Here, we analysed CK2 during adipogenic differentiation of human mesenchymal stem cells (hMSCs). With progress of the differentiation CK2 protein level and the kinase activity decreased. Whereas CK2α remained in the nucleus during differentiation, the localization of CK2β showed a dynamic shuttling in the course of differentiation. Over the last years a large number of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 73 publications
(25 reference statements)
3
14
0
Order By: Relevance
“…However, other possibilities should be also taken into account. In accordance with our results, Schwind and colleagues have recently published a paper [ 23 ] where the inhibition by CX-4945 and its effects on stem cell differentiation were found to decrease from 24 h to 72 h. Since in that case the inhibitor was maintained in contact with cells for all the length of the experiment, the result would indicate that its effective concentration decreased, and this could be due to several causes, such as compound extrusion, subcellular redistribution, or metabolic inactivation.…”
Section: Discussionsupporting
confidence: 92%
“…However, other possibilities should be also taken into account. In accordance with our results, Schwind and colleagues have recently published a paper [ 23 ] where the inhibition by CX-4945 and its effects on stem cell differentiation were found to decrease from 24 h to 72 h. Since in that case the inhibitor was maintained in contact with cells for all the length of the experiment, the result would indicate that its effective concentration decreased, and this could be due to several causes, such as compound extrusion, subcellular redistribution, or metabolic inactivation.…”
Section: Discussionsupporting
confidence: 92%
“…After day six of differentiation, inhibition of CK2 activity demonstrated no effect on the differentiation process. Very similar results were reported for the adipogenic differentiation of human mesenchymal stem cells (62). In this case it was, however, shown that mesenchymal stem cells respond differently to the type of inhibitor for the CK2 enzyme activity.…”
Section: Ck2 and Adipogenic Differentiationsupporting
confidence: 86%
“…For instance, Hu and Wieloch [31] found that distinct brain regions are protected by an increased CK2 activity against ischemic cell death. These findings are in line with the well-known antiapoptotic function of CK2 [32]. Moreover, Mottet et al [33] reported that CK2 positively regulates hypoxia-inducible factor 1 activity in tumor cells, mediating their adaptation to hypoxia.…”
Section: Discussionsupporting
confidence: 74%